Site-Specific Gut Microbial Signatures in Non-Celiac Gluten Sensitivity - Kunal Dixit; Anam Ahmed; Alka Singh; Mitali Inamdar; Sonal Chavan; Rahul Bodkhe; Wajiha Mehtab; Ashish Chauhan; Sunil D. Saroj; Vineet Ahuja; Yogesh Shouche; Dhiraj Dhotre; et al. (Gut Microbes Reports, 2024)
Gut microbiota in non-celiac gluten sensitivity (NCGS) has been poorly studied for its involvement in the disorder and site specificity. We investigated small intestinal, large intestinal and stool microbiota profiles in patients with NCGS and highly overlapping disorder irritable bowel syndrome (IBS) as well as effect of gluten-free diet (GFD) on microbiota in patients with NCGS. True NCGS patients were recruited based on serological response for anti-gliadin antibodies, 6-week gluten free diet (GFD) and symptom recurrence with gluten-rechallenge. Analyses using 16S rRNA gene amplicon and shotgun sequencing revealed community differences in core microbiome and diversity measures across sample types indicating dysbiosis mainly in mucosa-associated small intestinal microbiome of NCGS patients. Genera Elusimicrobiaum, Succinivibrio, Bacillus and Alcaligenes appeared as signatures in small intestine and stool in NCGS patients. Presence of differential taxa co-occurring at sampling sites, enabled recognition of site-specific microbial signatures. GFD led to a shift in mucosa-associated small intestinal core microbiome. Metagenome analysis revealed subtle differences in pathways for amino acid biosynthesis including L-ornithine. Mucosa-associated small intestine microbial structure was quite distinct in patients with NCGS in comparison to that with IBS.